The Employment, Unemployment and Unemployment Compensation Benefits of Immigrants - Michael E. Hurst; Barry R. Chiswick (Institute for the Study of Labor (IZA), 2000)
This report analyzes the employment and unemployment experiences of adult foreign-born men, both among themselves and in comparison with the native born. The empirical analysis uses microdata from the 1990 Census of Population. Three dependent variables are analyzed, weeks worked (employment) in 1989, unemployment status in the reference week in 1990, and a proxy measure of unemployment compensation benefits received in 1989. The theoretical model focuses on the job search behavior of the foreign born within the context of an immigrant adjustment model based on the imperfect transferability of skills and labor market information acquired prior to immigration. In particular, the model focuses on the effects on employment and unemployment of schooling, labor market experience, marital status and the agricultural sector, in addition to English language fluency and country of origin. The hypotheses developed from the model are found to be consistent with the data. Employment is significantly lower, and unemployment is significantly higher, among the foreign born in the U.S. for three or fewer years, but then reaches a level after which there is little variation by duration of residence. Unemployment problems associated with immigrants appear to be short-term transitional adjustments.
Keywords: J61; 330; Adjustment process; language fluency; country of origin; Migranten; Erwerbsverlauf; Arbeitslosigkeit; Dauer; Arbeitsuche; Humankapital; Arbeitslosenversicherung; Schätzung; USA